Part 1: Supporting the Reduction of Suicide in the General Population of Wales via the use of Structured Professional Judgement; Part 2: Identifying the Factors Moderating Suicidal Thoughts and Suicide Attempts During the COVID-19 Pandemic. - JAMES KNOWLES (2023)
Part 1: Early identification of individuals at risk of suicide represents a crucial component of effective suicide prevention. However, many of the current suicide risk assessment procedures are limited in their ability to identify and prevent future suicide attempts. This thesis aimed to investigate whether the structured professional judgement approach was an effective method of suicide risk assessment within an accident and emergency department. Chapter 1 outlined the major challenges facing the field of suicide risk assessment and introduced the structured professional judgement approach to risk assessment. Chapter 2 reviewed the various methods used to assess the risk of suicide within accident and emergency services, evaluated the efficacy of the structured professional judgement approach and outlined the new structured professional judgement scheme, the Risk of Suicide Protocol, that was investigated in this thesis. Chapter 3 compared the Risk of Suicide Protocol and assessment as usual in their ability to identify future suicide attempts in 107 participants referred for a suicide risk assessment with the accident and emergency-based Psychiatric Liaison Team. Chapter 3 also evaluated the inter-rater reliability of the Risk of Suicide Protocol, with two independent assessors completing assessments on the same 12 patients. Chapter 7 reviewed the research relating to the RoSP and discussed the wider meaning and clinical implications of the findings. The findings demonstrated that risk judgements made using the Risk of Suicide Protocol were significantly better at identifying future suicide attempts compared to assessment as usual. Additionally, the risk judgements made using the Risk of Suicide Protocol demonstrated excellent inter-rater reliability. These results indicate that the Risk of Suicide Protocol is a valid and reliable assessment for the structured clinical evaluation of suicide risk within an accident and emergency department. Overall, this thesis demonstrates that the Risk of Suicide Protocol represents a valuable method for the evaluation of suicide risk and may offer an important solution to some of the challenges facing the field of suicide risk assessment. Part 2: The COVID-19 pandemic resulted in a wide range of difficulties for populations across the world, with research indicating that the pandemic had negatively impacted population mental health. This thesis aimed to identify and understand the factors influencing suicidal thoughts and attempts during the COVID-19 pandemic. Chapters 1 and 4 reviewed how the COVID-19 pandemic affected population mental health and suicidality and explored the rationale for this research. Chapters 5 and 6 reported the results of an online survey administered to a large sample of adults (N > 13,000) living in Wales between the 18th of January 2021 to the 7th of March 2021. Chapter 5 aimed firstly, to identify the demographic groups most vulnerable to suicidal thoughts and attempts and secondly, to examine whether various pandemic related stressors (e.g., social isolation, food insecurity) were associated with suicidal thoughts and attempts. Chapter 6 investigated whether hope, social connectedness, resilience or pandemic acceptance could protect against the presence of suicidal thoughts during the COVID-19 pandemic. Chapter 7 reviewed the research and considered the wider implications of the findings. The findings from chapter 5 revealed that men, younger adults and socioeconomically deprived individuals were more likely to experience suicidal thoughts during the pandemic, with younger adults also more likely to attempt suicide. Chapter 5 also found that domestic abuse, food insecurity, difficulty accessing healthcare, social isolation, relationship problems, financial problems and being made redundant were the pandemic related stressors most strongly related to suicidal thoughts and attempts. Chapter 6 found that hope, resilience and pandemic acceptance all protected against suicidal thoughts during the pandemic, with higher levels of hope, resilience and pandemic acceptance weakening the relationship between pandemic stress and suicidal thoughts. Overall, this thesis has enhanced our understanding of the factors influencing suicidal thoughts and attempts during the COVID-19 pandemic. The findings provide valuable insights that can be used to inform outreach and support structures in their efforts to prevent suicide.